ANDROID CHARACTER GAME BASED ON THE STORY OF THE PROPHET'S FRIENDS AS AN EFFORT TO BUILD STUDENT CHARACTER AT SCHOOL - SULTAN FAKHRUR RASSYI SULTAN; Isro’ullaili Isro’ullaili (FKIP Universitas Samawa, 2023)
Character education has always been a controversial topic and an ongoing issue, particularly in Indonesia. The problems related to the rise of criminal incidents such as murder, robbery, fraud, corruption, violence, student brawls, and even cases involving underage perpetrators have persisted without a clear resolution from the government. Many sources point out that these issues stem from the lack of character education in Indonesia, both for children and adults. The deficiency in character education is considered problematic as it can lead to a deterioration of morals, especially among the future generations of the nation. Hence, a solution is needed to aid the government in addressing this issue, leveraging technological advancements and employing methods suitable for all age groups. An innovative solution has emerged in the form of an application called